EVALUASI PROGRAM JAMPERSAL DI KABUPATEN PEKALONGAN TAHUN 2011 - Maslekhah .; Priyatno Harsasto; Lusia Astrika (Journal of Politic and Government Studies, 2013)
The purpose of this study was to determine the extent of the Implementation Process Jaminan Persalinan Program in Pekalongan and to find out why Pekalongan Less Achieve MDG Target's Policy Delivery Guarantee Program is a program of the Central Government's Ministry of Health Reublik Indonesia. Evaluation process used to determine program execution Jaminan Persalinan in Pekalongan descriptively analyzed by looking at the phenomenon that is happening in the community. Looking at the various aspects that have been analyzed can be concluded that there are still barriers and obstacles in the implementation of the Programme Jaminan Persalinan